READING STRATEGIES IN EFL CLASSROOM: A THEORETICAL REVIEW - Teguh Budiharso (Center of Language and Cultural Studies, 2014)
Teaching reading has been long discussed in the context of English teaching curriculum in Indonesia. The ground of English curriculum (e.g. 1984, 1994, 2004 English curriculum) lays reading as the main model of teaching English in the secondary school across classroom levels. Many English teachers have been occupied with the concepts and perceive that some concepts in teaching reading are interchangeable with reading strategies. This paper tries to give review on the reading definition, reading models, reading strategies, teaching reading, and model of teaching reading in the communicative context. The reading models present psycholinguistics model and schema theory models. The strategies of reading discuss bottom up, top-down, and interactive strategies. Strategies in teaching reading deal with reading for information, mapping, skimming and scanning. The article is closed with teaching techniques covering pre-reading, while reading, and post-reading.